EU-China bilateral investment relations: How can the European Union deal with the Chinese investment offensive? - Bahri Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
China and Europe are two global economic powers and essential parts of the international value chain. Companies on both sides are interested in taking advantage of the opportunities offered by the European and Chinese markets in the form of creating jobs, inducing innovation, and extending their markets. China's rapid development has benefited greatly from the capital, technology, and know-how of European companies. For EU companies, China is no longer only an important location for the production of intermediate goods and raw materials, a supplier, or sales market, but it is also considered of great importance as a research and development location. The main aim of this paper is to examine EU-China investment relations. In the first part of our work, we will focus on the overall view of the development of Chinese FDIs in the EU and vice-versa. Then, we will deal with the distribution of Chinese FDIs in the EU according to member states and economic sectors. In the last part, we will discuss the main concerns between Brussels and Beijing regarding the Chinese investment offensive on Europe and its consequences for both sides. In this respect, we focus on a new EU-level screening framework implemented mainly against Chinese investments in Europe.
Keywords: 330; China; European Union; Foreign Direct Investments; Portfolio Investments